Employee reactions to leader emotional display strategies in a crisis situation - Lynn Schmodde; Marius Claus Wehner (European Management Review, 2023)
During a crisis, leaders experiencing fear have to decide whether to reveal or regulate their emotions. Drawing on the emotions as social information (EASI) model and employing an experimental vignette study (n0.167em=0.167em159) in the context of a young firm's crisis, we compare employee reactions (i.e., employee affect, job engagement, and affective commitment) to different leader emotional display strategies, namely, deep acting, surface acting, and genuine emotions. Compared with a leader's genuine emotions (i.e., display of fear), surface acting increased negative affect, whereas deep acting reduced negative affect. With regard to the total effects of our mediation model, surface acting negatively influenced employee job engagement and affective commitment, whereas deep acting surprisingly showed no differences to the display of genuine emotions. Our findings indicate that leaders who experience fear may consider revealing this genuine emotion during a crisis rather than engaging in potentially inauthentic emotion regulation strategies.
Keywords: 650; crisis; emotion regulation; experimental vignette study; genuine emotions; leader authenticity; leadership